1983
DOI: 10.1099/0022-1317-64-4-833
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure Analysis of Pichinde Virus Nucleocapsids

Abstract: The structure and organization of the ribonucleoprotein (RNP) complex of an arenavirus, Pichinde virus, was investigated. The basic configuration of the RNP was found to be a linear array of globular subunits or nucleosomes, 4 to 5 nm in diameter, that represent individual molecules of the major N polypeptide. This filament appears to fold progressively through a number of intermediate helical structures, 12 to 15 nm in diameter, that reveal an increasing number of nucleosomes associated with each turn of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0
3

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 0 publications
8
43
0
3
Order By: Relevance
“…The phlebovirus RNPs have some of the smallest N proteins and represent the extreme of asymmetry among a range of architectures displayed by RNPs of negative-sense viruses. The arenaviruses also have an asymmetric RNP (4,12), but the N protein is unrelated to the phlebovirus N and has an additional exoribonuclease domain (20,21). The RNP architecture is understood in greatest detail for those viruses with RNP of highest symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The phlebovirus RNPs have some of the smallest N proteins and represent the extreme of asymmetry among a range of architectures displayed by RNPs of negative-sense viruses. The arenaviruses also have an asymmetric RNP (4,12), but the N protein is unrelated to the phlebovirus N and has an additional exoribonuclease domain (20,21). The RNP architecture is understood in greatest detail for those viruses with RNP of highest symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The two nucleocapsids are beaded, loosely helical structures (9-15 nm in diameter). They each form a closed smaller (400-600 nm) or larger (1000-1300 nm) circle depending on whether they contain the S or L RNA, respectively (Young and Howard, 1983). Virions are frequently genetically diploid.…”
Section: Viral Genome Organizationmentioning
confidence: 99%
“…S2), indicating that the majority of r3LCMV CAT/GFP infectious virions contained both (GPC-GFP and CAT-NP) S segments. There are some precedents based on both genetics (9) and structural (10,31) analysis in support of S polyploidy within arenavirus infectious particles. Our data showed that preparations of infectious particles from LCMV WT and r3LCMV were undistinguishable either by size or shape, but we were unable to determine precisely the percentage of particles with two or three segments present within the r3LCMV population.…”
Section: Bhk-21 Cells (Ifn -mentioning
confidence: 99%